Epistemological and ontological shifts to rethink the debate around cultural heritage - Alegrìa Licuime, Luis; Galeno Ibaceta, Claudio; Stefoni Espinoza, Carolina (Huarte de San Juan. Geografía e Historia, 2025)
To what extent and in what ways can we identify certain ruptures with the hard, heavy, systemic, and organic matrix of cultural heritage—reproduced and self-reproduced—expressed in the ideas of monuments, tradition, or relics, which conceive it as a unique, sacred, and imperishable expression of society, particularly Western society? The term «turn» refers to a significant change or shift in a particular discipline, field of study, or new conceptual approach. It is important to note that some of these turns come to constitute true epistemic ruptures within a discipline or field of study, challenging the constitutive and dominant paradigms of the sciences. We propose analyzing the five turns that are currently affecting the field of cultural heritage: the historical, participatory, feminist, decolonial, and ontological turns, which constitute key theoretical breaks for rethinking cultural heritage today.
Keywords: epistemological turn; participation; feminism; decolonial; ontology